Influence of Solar Radiation on the Environment of Uzbekistan - Suvonova, G. A.; Mamatkulov, J. J.; Khamdamova, E. I. (American Journal of Biology and Natural Sciences, 2025)
Countries with arid climates such as Uzbekistan have critical interaction between the solar radiation and the environment. Although there have been global studies of solar energy’s related environmental impacts, there is a knowledge deficit of the exact ecological effects of solar radiation in Uzbekistan’s various climatic regions. Using a mixed method approach, this paper collects data on 2010–2023 quantitatively from meteorological proxies, and uses remote sensing analysis to measure three key indicators: soil temperature, vegetation health, and atmospheric transparency. The findings show an apparent correlation between increased solar radiation intensity and environmental degradation including soil desiccation, vegetation stress and desertification, especially in desert and semi desert zone. Maps were made for seasonal and regional variations in the exacerbations of radiation effects, which show that radiation effects are exacerbated in summer months because of lower atmospheric transparency and higher aerosol concentrations. In addition, the results support the view that unregulated solar exposure accelerates ecological stress, and thus highlight the importance of adaptive land planning and climate resilience strategies, in Uzbekistan. The insights presented here offer a critical foundation to policymakers’ considerations of solar energy development and environmental sustainability.